A influência da habilitação em serviço na prática do/a professor/a - Maria Cecilia de Medeiros Abras (1998)
This Work analyses the processes of the change that may have occurred in the pedagogic practice after an in-job formation. The research is of a qualitative nature, based on the oral reports of nine lay student-teachers that attended the Emergential Courses promotated by PUC/MG in partnership with SSE/MG and of other members of the schools where these people tech. The theory used for the analysis was based on studies on teacher formation under a sociological perspective. The Emergential Courses consists of a kind of activity for the qualification of lay people who work as teachers. The course gives out short graduation and graduation certificates to answer for the great need from regions where there are a large body of lay teachers. This work aims contributing to the formation of the lay teacher, in a critical way, in regard to the rescue of the necessary competence in order to act in a thoughtful and reflexive manner and not only worrying about the knowledge of the pedagogical proposal of Emergential Programmes.